The Rise of Ethno-nationalism in the Globalisation Era: Comparative Analysis of AfD Germany and BJP India - Vany Fitria (Andalas Journal of International Studies (AJIS), 2024)
As integral components of the global movement, both nationalism and globalisation play significant roles in the rise of ethno-nationalism, particularly influenced by the emergence of social media. Today, nationalist populist figures can easily and extensively disseminate their values through various social media platforms, effectively turning this technology into an echo chamber for ethno-nationalist leaders. Their strategy to spread influence often involves promoting xenophobic propaganda narratives that glorify their supreme goals and identity while alienating minorities perceived as threats. This article critically examines the rise of ethno-nationalism, and the crucial role played by social media, focusing on two political parties: the Alternative for Germany (AfD) in Germany and the Bharatiya Janata Party (BJP) in India. Using qualitative descriptive methods and a case study approach, this research reveals that in both cases, ethno-nationalist leaders utilise Islamophobic populism by alienating Islam and framing Muslims as "the other." Furthermore, social media serves as a critical tool for ethno-nationalist parties to spread their agenda and strengthen connections with their supporters.